The content of nutrients and biogenic elements in enriched artemia salina - Sveshnikova Elena; Romanova Elena; Fazilov Elyor; Romanov Vasily; Turaeva Elena; Shlenkina Tatyana; Lyubomirova Vaselina (E3S Web of Conferences, 2023)
The work is devoted to the development of technology for enriching artemia with biologically active substances. The development of technology for enriching artemia with biologically active substances is important as an opportunity to obtain starter feeds for aquaculture with the desired properties. High content of high-grade protein, vitamins, amino acids, fatty acids, biogenic elements is of great importance. During artificial cultivation of artemia in a closed cycle in the conditions of aquaculture, there is a problem of sufficient accumulation of substances in its body that provide high nutritional and biological value. To solve this problem, we have developed a technology for enriching artemia with biologically active substances at the nauplium stage. The enrichment of artemia with vitamins, amino acids, probiotics, adaptogens, essential lipids allows us to create a new generation of bio-feeds containing a living symbiotic microbiota and ingredients capable of forming balanced complex of functional nutrition for fish. The aim of the study was to evaluate the biological and energy value, the content of proteins, fats, carbohydrates, moisture, ash, micro- and macroelements, heavy metals in artemia at different stages of ontogenesis against the background of its enrichment with a complex of biologically active substances. Intact and enriched cysts, intact and enriched decapsulated artemia eggs, enriched artemia nauplii were analyzed. It was found that against the background of enrichment with biologically active substances, the indicators of metabolic energy increased, the mass fraction of crude protein, the mass fraction of fat and the content of minerals and biogenic elements increased.